LABORATORY FEATURES OF URATE NEPHROPATHY IN CHILDREN - Gapparova Guli Nurmuminovna (Western European Studies, 2024)
The interest in the study of urate nephropathies in children is determined by the following points: the significant prevalence of CHI diseases in both the pediatric and adult populations, the global trend towards an increase in the frequency of chronic kidney disease (CKD) and chronic renal failure (CRF) despite all the achievements of modern clinical nephrology
Keywords: nephropathy; children; oxalaturia